Корупційні ризики в логістиці підприємств: інструменти запобігання та їх вплив на конкурентоспроможність - Нісфоян, Сергій Сергійович; Немненко, Анастасія Андріївна (Національний технічний університет "Харківський політехнічний інститут", 2025)
Стаття присвячена дослідженню теоретико-методологічних засад і практичних аспектів подолання корупційних ризиків у сфері логістики підприємств та їхньому впливу на конкурентоспроможність. Розкрито сутність корупційних проявів у логістичних процесах, охарактеризовано їх форми на різних етапах логістичного ланцюга: постачання, складання, транспортування, митного оформлення та реалізації продукції. Виокремлено найбільш уразливі для зловживань ділянки, зокрема вибір постачальників, укладання контрактів, управління запасами та взаємодію з контролюючими органами. Обґрунтовано вплив таких ризиків на витрати, репутацію та інвестиційну привабливість підприємств, що функціонують в умовах відкритої конкуренції. Проаналізовано сучасні інструменти запобігання корупційним проявам у логістиці, зокрема, впровадження системи комплаєнсу, сертифікації антикорупційного менеджменту відповідно до стандарту ISO 37001, цифровізація логістичних процесів, автоматизація закупівель, застосування систем контролю як ключового елементу системи запобігання зловживанням. Наведено практичні кейси з українського та міжнародного бізнес-середовища, які демонструють ефективність або недосконалість існуючих підходів у запобіганні корупційним практикам. Розглянуто вплив корпоративної культури доброчесності на формування довгострокової конкурентної переваги підприємств. Особливу увагу приділено взаємозв’язку між зниженням корупційних ризиків і підвищенням конкурентоспроможності: шляхом оптимізації витрат, зростання рівня довіри з боку партнерів, інвесторів і споживачів, формування сталої репутації, зменшення регуляторного тиску. Оцінено вплив антикорупційних заходів на ефективність логістичних рішень, адаптивність підприємств до глобальних викликів, а також на інтеграцію у міжнародні ланцюги постачань. Аргументовано необхідність стратегічного підходу до управління доброчесністю у логістиці, що передбачає синергію технологій, внутрішнього регламентування, навчання персоналу та партнерства з державними й недержавними інституціями. Доведено, що впровадження комплексної антикорупційної політики у сфері логістики створює сприятливі передумови для формування ефективних, стійких і конкурентоздатних логістичних систем підприємств. У контексті післявоєнного відновлення економіки України та інтеграції до європейського ринку подолання корупційних ризиків у логістиці виступає ключовою умовою не лише ефективного функціонування бізнесу, а й національної економічної безпеки. Доповненої уваги заслуговує кадровий аспект забезпечення антикорупційної стійкості логістичних систем. Виявлено, що ключову роль у зниженні корупційних ризиків відіграє підвищення кваліфікації працівників, формування антикорупційної свідомості ,чіткий розподіл обов’язків і впровадження внутрішніх етичних кодексів. Запропоновано рекомендації щодо формування компетентнісного профілю логіста з урахуванням вимог доброчесності: здатність ідентифікувати ризики, застосовувати інструменти прозорості, взаємодіяти з системами електронного моніторингу. Зроблено висновок про доцільність інтеграції антикорупційного компонента в системи управління якістю підприємств та програми підготовки логістичних фахівців на рівні вищої освіти. The article is devoted to the study of theoretical and methodological foundations and practical aspects of overcoming corruption risks in the logistics sector of enterprises and their impact on competitiveness. The essence of corruption manifestations in logistics processes is revealed; their forms at various stages of the supply chain—procurement, warehousing, transportation, customs clearance, and product sales—are characterized. The most vulnerable areas to abuse are highlighted, including supplier selection, contract negotiation, inventory management, and interaction with regulatory authorities. The negative consequences of corruption risks on operational costs, reputational image, and investment attractiveness of enterprises operating under conditions of open competition are substantiated. Modern tools for preventing corruption in logistics are analyzed, particularly the implementation of compliance systems, certification of anti-corruption management according to ISO 37001, digitalization of logistics processes, automation of procurement, the use of AI-based control systems, logistics operations auditing, and ensuring transparency through blockchain technologies. The role of internal control as a key element of corruption prevention is disclosed. Practical case studies from Ukrainian and international business environments are presented to demonstrate the effectiveness or shortcomings of existing approaches in counteracting corruption practices. The impact of an organizational culture of integrity on the long-term competitive advantage of enterprises is examined. Special attention is paid to the correlation between reducing corruption risks and enhancing competitiveness. It is shown that reducing corruption contributes to optimizing costs, increasing the level of trust from partners, investors, and customers, improving the enterprise’s reputation, and reducing regulatory pressure. The article assesses the influence of anti-corruption measures on the efficiency of logistics decisions, enterprise adaptability to global challenges, and integration into international supply chains. The need for a strategic approach to integrity management in logistics is argued, involving a synergy of technological solutions, internal regulations, employee training, and partnerships with governmental and non-governmental institutions. A separate focus is placed on the human resources dimension of ensuring the anti-corruption sustainability of logistics systems. The article reveals that enhancing employee qualifications, developing anti-corruption awareness, implementing ethical codes of conduct, and clearly defining roles and responsibilities are all critical to mitigating risks. Recommendations are provided regarding the formation of a competence profile for logistics specialists in the context of integrity requirements: the ability to identify risks, apply transparency tools, interact with electronic monitoring systems, and use modern digital platforms. The study emphasizes the relevance of integrating anti-corruption elements into enterprise quality management systems and higher education programs for logistics professionals. It proposes the inclusion of anti-corruption training modules in professional development and university curricula to cultivate a new generation of specialists capable of resisting unethical practices and maintaining transparency throughout the supply chain. Moreover, the research highlights the importance of developing regulatory support and policy measures at the national level to encourage transparent business practices in the logistics sector. Legislative initiatives aimed at simplifying administrative procedures, digital transformation of customs and procurement processes, and ensuring public access to data on logistics contracts and tenders are identified as critical factors in shaping a competitive and corruption-resistant business environment. The article also explores the implications of post-war recovery and European integration for the Ukrainian economy, emphasizing that the elimination of corruption risks in logistics is not only a matter of business efficiency but also a fundamental prerequisite for national economic security. The implementation of comprehensive anti-corruption strategies in the logistics sphere creates favorable preconditions for the formation of effective, resilient, and competitive enterprise logistics systems. In this context, the authors conclude that fighting corruption in logistics must become an integral part of the strategic management of enterprises, involving all levels of decision-making and operational execution. Strengthening integrity, improving transparency, and embedding preventive mechanisms into logistics management processes will ensure sustainable growth and better global integration of Ukrainian enterprises in the long run. Additionally, the study emphasizes the role of public-private cooperation in shaping a transparent logistics ecosystem. It argues that joint initiatives between business associations, civil society organizations, and governmental bodies can foster accountability and minimize opportunities for corruption. By establishing independent monitoring mechanisms, engaging stakeholders in policy dialogue, and promoting best practices across industries, Ukraine can accelerate its progress toward a resilient and corruption-free logistics sector. Such partnerships are especially important in the context of Ukraine’s accession to the EU, where adherence to strict transparency and compliance standards is both a prerequisite and a strategic advantage.
Corruption risks in enterprise logistics: prevention tools and their impact on competitivess
Keywords: логістика підприємств; антикорупційна політика; доброчесність; корупційні ризики; внутрішній контроль; конкурентоспроможність; комплаєнс; цифровізація логістики; блокчейн; логістичний менеджмент; enterprise logistics; anti-corruption policy; integrity; corruption risks; internal control; competitiveness; compliance; digitalization of logistics; blockchain; logistics management